2014
DOI: 10.1111/anae.12592
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of the i‐gel™ and the Laryngeal Mask Airway Classic™ in infants

Abstract: SummaryWe performed a randomised comparison of the i-gel TM and the Laryngeal Mask Airway (LMA) Classic TM in children aged less than a year who were undergoing general anaesthesia for elective surgery. Fifty-four infants were randomly allocated to either the i-gel or the LMA Classic. We measured performance characteristics, fibreoptic views through the device and complications. Success rate at first insertion attempt was 100% (27/27) in the i-gel group compared with 88% (23/26) in the LMA Classic group. Inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 18 publications
5
52
1
Order By: Relevance
“…[3,4,31] The i-gel can be considered as a reasonable candidate for meeting this requirement due to its noninflatable cuff and design for easy insertion. [32] Meta-analyses to secure evidence for the superiority of the i-gel have been carried out primarily in the field of anesthesia. A meta-analysis of the adult-sized i-gel under general anesthesia demonstrated that the i-gel had a shorter insertion time than other devices.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,31] The i-gel can be considered as a reasonable candidate for meeting this requirement due to its noninflatable cuff and design for easy insertion. [32] Meta-analyses to secure evidence for the superiority of the i-gel have been carried out primarily in the field of anesthesia. A meta-analysis of the adult-sized i-gel under general anesthesia demonstrated that the i-gel had a shorter insertion time than other devices.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies by Goyal et al [6] and [10] Unclear Unclear High* Unclear Kus et al [11] Unclear Unclear High* Unclear Gasteiger et al [12] Low Unclear High* Low † Goyal et al [6] Low Unclear High* Unclear Fukuhara et al [13] Low Unclear High* Unclear Das et al [7] Low Unclear High* Unclear Das et al [8] Low Unclear High* Unclear Lee et al [22] Unclear Unclear High* Unclear Theiler et al [18] Low Low High* Low † Tokgoz et al [14] Low Unclear High* Unclear Lee et al [16] Unclear Unclear High* Unclear Kim et al [17] Low Low High* Unclear Mitra et al [15] Low Unclear High* Unclear *Not possible to blind researchers to airway device used. †Intention to treat analysis stated.…”
Section: Oropharyngeal Leak Pressurementioning
confidence: 99%
“…The largest trial was by Lee et al [16]; they used devices of size 1.5-2.5 and found no significant difference in leak pressures between devices. Kim et al compared the i-gel with the LMA Classic in infants (children less than a year old) and found the i-gel easier to insert; otherwise the characteristics of both devices were similar [17].…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
“…[14,22] Since there was no PIP data available for i-gel, sample size was calculated based on a previous study using classic laryngeal mask airway in children. [10] In their study, the mean (standard deviation, SD) PIP of the PCV and VCV mode with a classic laryngeal mask airway were 14.1 (1.6) cm H 2 O and 16.7 (2.3) cm H 2 O, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, the incidence of gastric insufflation varied from 0% to 30% depending on the PIP and the presence of a gastric tube. [1214] …”
Section: Introductionmentioning
confidence: 99%